Reviews and notices - Michal Anne Moskov; Helena Bergmann; Karin Aijmer; Fritz Joachim Sauer; Frank Michael Kirsch; Tom Conner; Erik Cardelús; Jenny Norman (Moderna Språk)
Includes the following reviews: